ERICA: intake of macro and micronutrients of Brazilian adolescents - Amanda de Moura Souza; Laura Augusta Barufaldi; Gabriela de Azevedo Abreu; Denise Tavares Giannini; Cecília Lacroix de Oliveira; Marize Melo dos Santos; Vanessa Sá Leal; Francisco de Assis Guedes Vasconcelos (Universidade de São Paulo, 2016)
ABSTRACT OBJECTIVE To describe food and macronutrient intake profile and estimate the prevalence of inadequate micronutrient intake of Brazilian adolescents. METHODS Data from 71,791 adolescents aged from 12 to 17 years were evaluated in the 2013-2014 Brazilian Study of Cardiovascular Risks in Adolescents (ERICA). Food intake was estimated using 24-hour dietary recall (24-HDR). A second 24-HDR was collected in a subsample of the adolescents to estimate within-person variability and calculate the usual individual intake. The prevalence of food/food group intake reported by the adolescents was also estimated. For sodium, the prevalence of inadequate intake was estimated based on the Tolerable Upper Intake Level (UL). The Estimated Average Requirement (EAR) method used as cutoff was applied to estimate the prevalence of inadequate nutrient intake. All the analyses were stratified according to sex, age group and Brazilian macro-regions. All statistical analyses accounted for the sample weight and the complex sampling design. RESULTS Rice, beans and other legume, juice and fruit drinks, breads and meat were the most consumed foods among the adolescents. The average energy intake ranged from 2,036 kcal (girls aged from 12 to 13 years) to 2,582 kcal (boy aged from14 to 17 years). Saturated fat and free sugar intake were above the maximum limit recommended (< 10.0%). Vitamins A and E, and calcium were the micronutrients with the highest prevalence of inadequate intake (> 50.0%). Sodium intake was above the UL for more than 80.0% of the adolescents. CONCLUSIONS The diets of Brazilian adolescents were characterized by the intake of traditional Brazilian food, such as rice and beans, as well as by high intake of sugar through sweetened beverages and processed foods. This food pattern was associated with an excessive intake of sodium, saturated fatty acids and free sugar.